Perceptions of Surgery Residents About Parental Leave During Training - Altieri, Maria S. (JAMA Surg, 2019)
IMPORTANCE: To our knowledge, there has been little research conducted on the attitudes of residents toward their pregnant peers and parental leave. OBJECTIVE: To examine the perceptions of current surgery residents regarding parental leave. DESIGN, SETTING, AND PARTICIPANTS: A 36-item survey was distributed to current US general surgery residents and residents in surgical subspecialties through the Association of Program Directors in Surgery listserv and social media platforms. Questions were associated with general information/demographics, parental leave, having children, and respondents’ knowledge regarding the current parental leave policy as set by the American Board of Surgery. The study was conducted from August to September 2018 and the data were analyzed in October 2018. MAIN OUTCOMES AND MEASURES: Main outcomes included the attitudes of residents toward pregnancy and parental leave, parental leave policy, and the association of parental leave with residency programs. RESULTS: A total of 2188 completed responses were obtained; of these, 1049 (50.2%) were women, 1572 (75.8%) were white, 164 (7.9%) were Hispanic/Latinx, 75 (3.6%) were African American, 2 (0.1%) were American Indian or Alaskan Native, 263 (12.7%) were Asian, and 5 (0.2%) were Native Hawaiian or Pacific Islander. From the number of residents who had/were expecting children (581 [28.6%]), 474 (81.6%) had or were going to have a child during the clinical years of residency. Many residents (247 [42.5%]) took fewer than 2 weeks of parental leave. Many residents did not feel supported in taking parental leave (177 [30.4%] did not feel supported by other residents and 190 [32.71%] did not feel supported by the faculty). Only 83 respondents (3.8%%) correctly identified the current American Board of Surgery parental leave policy. Residents who took parental leave identified a lack of a universal leave policy, strain on the residency program, a loss of education/training time, a lack of flexibility of programs, and a perceived or actual lack of support from faculty/peers as the top 5 biggest obstacles to taking leave during the clinical years of residency. CONCLUSIONS AND RELEVANCE: Most of the modifiable factors that inhibit residents from having children during residency are associated with policies (eg, a lack of universal leave policy and lack of flexibility) and personnel (eg, a strain on the residency program and lack of support from peers/faculty). These data suggest that policies at the level of the Accreditation Council for Graduate Medical Education or Resident Review Committee (RRC), as well as education and the normalization of pregnancy during training, may be effective interventions.